Markets as Fields: an Attempt to Reconceptualise - Yudin*Greg (Journal of Economic Sociology, 2010)
The author considers the idea of markets as fields not only to add to the list of metaphors for the market but to suggest some phenomenology and construct the object adequately. In sociology there were done several attempts to conceptualize markets as fields and now the idea of these fields as object of analysis became a usual thing in sociology. Putting more close relation between these attempts and phenomenological main theory of fields will allow to implement necessary changes and have more grounded result.